Astragaloside IV- loaded heart-mitochondria dual-targeted nanomicelles improved heart injury after acute myocardial infarction - Yang Ke; Li Lan; Fan Guanwei (生物医学转化, 2022)
Acute myocardial infarction(AMI) is a serious threat to human health due to its high morbidity and mortality. Persistent myocardial injury remains after AMI, although the mortality of AMI has been greatly reduced by drugs, interventional therapy and surgery. Astragaloside IV(AST) is one of the main active components of Astragali Radix. However, the hydrophobicity of AST limits its bioavailability. In this experiment, we developed a platelet membrane-modified poly(d, L-lactic-Co-Glycolic Acid) -block(PLGA-b) -poly(Ethylene Glycol)(PEG) Triphenylphosphonium(TPP)(PLGA-b-PEG-TPP) polymer nanomicelles for encapsulating AST to achieve the dual targeting effect of ' heart-mitochondria ' from the ' organ-organelle ' level. In this study, the drugloaded nanomicelles were characterized by transmission electron microscope, dynamic light scattering, drug release and stability investigation. The cardiac targeting effect of drug loaded nanomicelles was confirmed by in vivo imaging. The effects of drug-loaded nanomicelles on cardiac function and myocardial injury after I/R were investigated by echocardiography, histology and serum enzymology. The effects of drug-loaded nanomicelles on cardiac mitochondrial function and inflammation were evaluated by examining mitochondrial morphology, membrane potential, reactive oxygen species(ROS)and levels of inflammatory factors in serum and heart. Compared with the free AST, the results showed that drug-loaded nanomicelles significantly improved cardiac function, myocardial injury, mitochondrial damage and cardiac inflammation after I/R . It was suggested that the drug loaded nanomicelles significantly improved the bioavailability and cardioprotective activity of AST. This experiment provides a new strategy for the delivery of hydrophobic active monomer of traditional Chinese medicine.